Overall survival in adult patients with low-grade, supratentorial glioma: Ten years’ follow up at a single institution - Kashi, Amir Shahram Yousefi (Electron Physician, 2015)
BACKGROUND: Low-grade gliomas (LGGs) are the second most prevalent type of primary brain tumors in adults. The prognosis for LGGs can differ according to the clinical-pathological prognostic factors determined during diagnosis and treatment. The purpose of this study was to identify 10-year, disease-free survival (DFS), 10-year overall survival (OS), and related clinical-pathological prognostic factors of adult patients with supratentorial, low-grade gliomas who were treated with or without surgery and radiation therapy. METHODS: The study included 110 patients who were confirmed to have low-grade, supratentorial gliomas and who had received surgery and adjuvant radiation therapy or salvage radiotherapy as part of their treatment. These patients were followed by the radiation-oncology ward at Shohada-e-Tajrish Hospital in Tehran, Iran, between 2002 and 2012. The log-rank test (univariate) and the Cox proportional hazards model (multivariate) were used to examine the 10-year DFS and OS and to assess the strengths of various histo-clinical factors relative to 10-year DFS and OS. RESULTS: The study included 110 patients for whom 10-year DFS and OS were found to be 23 and 28%, respectively. Favorable prognostic factors in the univariate analysis using the Kaplan-Meier 10-year OS analysis were the following: age below 40, karnofsky performance status (KPS) more than 70, the presence of oligodendroglioma, tumor size of < 5 cm, and gross-total resection (p=0.02, p=0.01, p=0.03, p=0.01, p=0.02, respectively). Good prognostic factors in multivariate analysis using the Cox regression model were as follows: age below 40, the presence of oligodendroglioma, tumor size< 5 cm, and gross total resection in10-year OS (p=0.01, p=0.03, p=0.00, p=0.02, respectively). CONCLUSIONS: Gross-total resection, tumor size < 5 cm, age below 40, and the presence of oligodendroglioma had better 10-year DFS and OS rates. We recommend that all patients with LGG tumors be referred to neuro-oncology centers that have sufficient experience to achieve the best results of treatment.